Peranan Roh Kudus Dalam Pertumbuhan Gereja - Silakda, Selfina H.; Paparang, Stenly Reinal (PT. Bangun Harapan Bangsa, 2023)
The purpose of this paper is to know the growth of the Church and explain the Role of the Holy Spirit in the Growth of the Church. The research method used in this paper uses qualitative descriptive methods with a library research approach. This method is used to obtain information regarding the essential factors that play a role in influencing Church Growth and disclose information related to the subject under study, namely through the Bible and library research sources. Namely supporting books, various literature, and scientific journals relevant to research. The results reveal the Holy Spirit's role in the Church's growth. That the part of the Holy Spirit needs to be understood by Christians. Through the Holy Spirit God is personally present in the Christian. Therefore the Holy Spirit plays a vital role in the growth of the Church as the body of Christ as follows; Teaching believers, Convusing sinners, being born again, accompanying, comforting, enlightening, purifying, helping even giving gifts or abilities to every Christian. It also helps each other to grow His Church both inward and outward.